THE EFFECTIVENESS OF PERSUASIVE PREACHING (A STUDY IN THE ASPECTS OF COMMUNICATION PSYCHOLOGY) - Samsul Rani; Nahed Nuwairah; Amrullah; Bayani; Tarwilah (Journal International Dakwah and Communication, 2026)
The effectiveness of persuasive preaching in contemporary contexts demands a profound understanding of communication psychology mechanisms underlying the reception and transformation of religious messages. This study employs a Systematic Literature Review (SLR) method with PRISMA protocol to analyze ten journal articles from 2021-2025 addressing the integration of communication psychology in persuasive preaching. Results indicate that preaching effectiveness is determined by three psychological mechanisms: communicator credibility based on empathy (ethos), emotional connection through social proximity (pathos), and logical argumentation reducing cognitive dissonance (logos). Determinant factors include communicator empathy, understanding of audience’s hierarchy of needs, message contextualization, media adaptability, and therapeutic communication. Optimization of persuasive strategies requires responsiveness to cognitive modalities, emotional dynamics, and socio-cultural contexts of audiences. This study confirms that integrating communication psychology transforms preaching into a humanistic process achieving sustainable behavioral change and spiritual tranquility (sakinah) among contemporary audiences.